Constraints from in-situ Rb-Sr dating on the timing of tectono-thermal events in the Umm Farwah shear zone and associated Cu-Au mineralisation in the Southern Arabian Shield, Saudi Arabia. (February 2022) - Redaa, Ahmad; Farkaš, Juraj; Hassan, Ahmed; Collins, Alan S.; Gilbert, Sarah; Löhr, Stefan C.
Graphical abstract: Highlights: In-situ Rb-Sr dating constrains tectonic and igneous events in mineralised systems. Umm Farwah Major Shear Zone was developed between 671 Ma and 631 Ma. Ablah pegmatite was emplaced following the shear zone between 626 and 611 Ma. Greisen and Cu-Au deposits in the Mount Ablah were formed due to two separate hydrothermal events. Abstract: Constraining the tectonic history and timing of major shear zone structures in the Arabian Shield is critical for better understanding of the origin, tectonic history and distribution of ore deposits within this Precambrian crystalline crustal block. Here, we used a novel in-situ Rb-Sr dating of micas and K-feldspar to constrain the age of the Umm Farwah Shear Zone, which represents a regional tectonic feature that extends about 200 km across the southern part of the Arabian Shield. We also constrain the timing of Mount Ablah mineralisations which are exposed within the Umm Farwah Shear Zone and contains two styles of mineralisations including a greisen and Cu-Au mineralisation. These ore deposits are hosted in a pegmatite body that formed during the development of the Umm Farwah Shear Zone. Two main groups of muscovite (i.e., Group I and Group II) and K-feldspar mineral phases were identified based on ages and elemental variations in the mineralised zone and the host rocks. Results of in-situ Rb-Sr dating in the above K-rich minerals show that the Umm Farwah Shear Zone was initiated at ca. 651 Ma, and the emplacement of the Mount Ablah pegmatite occurred between 626 and 611 Ma, followed by the formation of greisen at 601 ± 12 Ma. In-situ Rb–Sr data also highlight a younger 'alteration' event occurred at ca. 556 ± 23 Ma, which partially reset the Rb–Sr system in the pegmatite and may thus reflect hydrothermal circulation event or overprint due to formation of Cu-Au mineralisation.